Repensando a prestação de contas públicas, à luz das teorias democrática e republicana: uma análise da responsividade pública enquanto modo operacional integrado pelos deveres fundamentais de motivação e de informação - Castro, João Vitor Cruz de (2023)
The research that originated this dissertation intended to investigate the state accountability, as an institute of constitutional law, in a way more focused on the Brazilian constitutionalism. With this, the objective was to outline an overview of what was chosen to be called the accountability system lato sensu, in order to present the classifications, categories and concepts that are understood to be the most relevant about this institute, focusing on the then called responsiveness operational mode, which is a pillar of the accountability integrated by the fundamental duties of motivation and of information of the public service (in all its types). Better explaining, the importance of revisiting the idea of a system of accountability stems from the need to advocate state control and to homage the theory of the mandate representation, as a way of expanding the correspondence between the performance of public functions and popular sovereignty, so that it is only believed to be viable from the emphasis on both fundamental duties in question. Still, it starts from the assumption that the notion of accountability can no longer be conceived under the same view that until then generally had, exclusively from a financial perspective, in the form of control of pecuniary public spending. No. The epistemological opening of the expression must be maximum, in order to encompass the public service completely, in relation to all public functions, including. In order to accomplish all of this, an analytical foreshortening of the democratic and republican theories was necessary, aiming to apprehend their main foundations, which are substantial to conceive a accountability system lato sensu capable of placing limits on the handling of power by public agents in general. At the end, conclusions were launched, in order to compare the ideas and assumptions firstly espoused with the results achieved throughout the research noted in this work, as well as with the aim of contributing in theoretical terms to the evolution of the constitutional institute detailed here. In addition, it is also stated that, as can already be inferred from this explanation, it was an exploratory and descriptive research, which used the observatory-inductive method, through a bibliographic technical procedure, carried out by means of data collection, that is, basically from a bibliographic review of the relevant literature, especially the constitutionalist one, being highlighted in this particular aspect books and scientific articles, as well as normative acts, especially laws in the strict sense